Patient- and parent-reported outcome measures of developmental adaptive abilities in visually impaired children: The Visual Impairment Developmental Autonomy (VIDA) scale. (December 2022) - Grumi, Serena; Morelli, Federica; Mascherpa, Eleonora; Decortes, Francesco; Luparia, Antonella; Provenzi, Livio; Signorini, Sabrina
Abstract: In the pediatric context, parents' and patients' engagement in the care process is strongly recommended and could be pursued using patient-reported outcome measures (PROMs), which therefore become useful for planning and monitoring treatments. Nevertheless, few data are available from families of children with neurodevelopmental disorders such as visual impairment (VI). The Visual Impairment Developmental Autonomy (VIDA) project aims to develop and validate a patient- and parent-reported tool to measure the most relevant aspects concerning everyday adaptive abilities in children and adolescents with visual impairment: the VIDA scale. The present paper illustrates the Delphi process of item generation engaging parents and patients and presents a protocol for the validation of this new co-designed tool in an Italian visually impaired pediatric population. Twenty-three families and five adolescents provided a list of 192 items and assessed their relevance. Items were categorized in 5 areas of adaptive abilities (i.e., table manners, clothing, personal hygiene, orientation and mobility, and socio-affectivity) and into three age ranges based on the patient's age. The final 102-item Vida Scale will be administered to a minimum of 300 visually impaired children together with measures of quality of life and child adjustment to investigate its psychometric properties. Highlights: Functional vision, related to the adaptive abilities, is still poorly studied. PROMs development and use are highly recommended in clinical practice. VIDA is a new PROM tool for adaptive abilities in visually impaired children. The paper presents the Delphi process of families engagement in item generation. In the VIDA project this new PROM tool will be validated.